Hybrid RANS/LES of plane jets impinging on a flat plate at small nozzle-plate distances - Kubacki, S.; Rokicki, J.; Dick, E.; Degroote, J.; Vierendeels, J. (Archives of Mechanics, 2013)
A k-ω based hybrid RANS/LES (Reynolds-averaged Navier-Stokes/large eddy simulation) model is tested for simulation of plane impinging jets at various nozzle-plate distances (H/B, where H is the distance and B is the slot's width) and various Reynolds numbers (based on the slot's width and the velocity in the symmetry plane). The studied combinations are H/B=2 for Re=10000, H/B=4 for Re=18000 and H/B=9.2 for Re=20000. The focus is on small distance of the nozzle exit to the plate. In LES mode, the hybrid RANS/LES model uses two definitions of the local grid size, one based on the maximum distance between the cell faces in the destruction term of the turbulent kinetic energy equation and one based on the cube root of the cell volume in the eddy-viscosity formula. This allows accounting for flow inhomogeneity on anisotropic grids. In RANS mode, the hybrid model turns into the newest version of the k-ω model by Wilcox.